Principles and practice of social marketing : an international perspective - Donovan, Rob, 1944-; Henley, Nadine (Cambridge : Cambridge University Press, 2010)
'This fully updated edition combines the latest research with real-life examples of social marketing campaigns the world over to help you learn how to apply the principles and methods of marketing to a broad range of social issues. The international case studies and applications show how social marketing campaigns are being used across the world to influence changes in behaviour, and reveal how those campaigns may differ according to their cultural context and subject matter. Every chapter is fully illustrated with real-life examples, including campaigns that deal with racism, the environment and mental health. The book also shows how social marketing influences governments, corporations and NGOs, as well as individual behaviour. The author team combine research and teaching knowledge with hands-on experience of developing and implementing public health, social welfare and injury prevention campaigns to give you the theory and practice of social marketing'--
Machine generated contents note: List of figures; List of tables; Preface; Acknowledgements; 1. Social marketing and social change; 2. Principles of marketing; 3. Social marketing and the environment; 4. Advocacy and environmental change; 5. Principles of communication and persuasion; 6. Models of attitude and behaviour change; 7. Research and evaluation; 8. Ethical issues in social marketing; 9. The competition; 10. Segmentation and targeting; 11. The marketing mix; 12. Using media in social marketing; 13. Using sponsorship to achieve changes in people, places and policies; 14. Planning and developing social marketing campaigns and programmes; 15. Case study: the Act-Belong-Commit Campaign promoting positive mental health; Index.
Includes bibliographical references and index.
Keywords: Social marketing; BUSINESS & ECONOMICS / Sales & Selling